2012
DOI: 10.1136/archdischild-2011-300646
|View full text |Cite
|
Sign up to set email alerts
|

Early diphtheria-tetanus-pertussis vaccination associated with higher female mortality and no difference in male mortality in a cohort of low birthweight children: an observational study within a randomised trial

Abstract: BackgroundStudies from low-income countries have suggested that diphtheria-tetanus-pertussis (DTP) vaccine provided after Bacille Calmette-Guerin (BCG) vaccination may have a negative effect on female survival. The authors examined the effect of DTP in a cohort of low birthweight (LBW) infants.Methods2320 LBW newborns were visited at 2, 6 and 12 months of age to assess nutritional and vaccination status. The authors examined survival until the 6-month visit for children who were DTP vaccinated and DTP unvaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 45 publications
(50 reference statements)
4
47
0
Order By: Relevance
“…In a recent paper by Aaby et al 21 have produced further data which attempt to control for nutritional status in an observational study, and confirm his previous findings on female infant mortality after DTP. While this concept may seem surprising, there are studies showing gender differences in innate immunity,22 adaptive immunity,23 autoimmunity24 and vaccine responses25 which provide some biological plausibility to the presence of differential effects of vaccines in relation to gender.…”
supporting
confidence: 62%
“…In a recent paper by Aaby et al 21 have produced further data which attempt to control for nutritional status in an observational study, and confirm his previous findings on female infant mortality after DTP. While this concept may seem surprising, there are studies showing gender differences in innate immunity,22 adaptive immunity,23 autoimmunity24 and vaccine responses25 which provide some biological plausibility to the presence of differential effects of vaccines in relation to gender.…”
supporting
confidence: 62%
“…The survival curves in the studies comparing DTP-vaccinated and DTP-unvaccinated children also indicate that there is no clustering of early deaths in the DTP group 142 53 64 Consistent with the tendency of nurses and physicians not to vaccinate sick children, current data suggest that DTP vaccination is associated with a strong positive selection bias, with healthier and wealthier children coming first for vaccination 142 53 64 Due to ‘frailty bias’ among the DTP-unvaccinated children, DTP should be expected to be associated with a beneficial effect on child survival.…”
Section: Resultsmentioning
confidence: 93%
“…Apart from reporting bias, the only proposed biases working in the opposite direction have been that starting follow-up after vaccination (as would happen with data from demographic surveillance systems) could mean that frail children had already died in the unvaccinated group leading to higher measured mortality in the DTP group; secondly, censoring for MV during follow-up could mean that the healthiest DTP-children were measles vaccinated first and the frail were left to die in the DTP group. It has been shown specifically in one study that the delay in starting follow-up had no impact on the estimate 27 and several studies have started follow-up at the time of DTP vaccination 23,26 and found similar strong negative effects, so there is no evidence that this bias is important. Similarly, the studies which have tested whether censoring for MV matters have found no effect 8 and many studies have not censored for MV and still found a strong negative effect of DTP 2,6,23,25,40 so there is no evidence that this bias is important.…”
Section: Methodsmentioning
confidence: 99%
“…We included seven studies of children (who had previously received BCG) that compared the mortality rate of DTP-vaccinated and DTP-unvaccinated girls 2,6,24-27,40 (Table 1); the bias index varied between 0.5 and 1.7 in these studies. These studies had some form of age-adjustment.…”
Section: Methodsmentioning
confidence: 99%